Upaya Meningkatkan Keaktifan Belajar Siswa Kelas VII Pada Mata Pelajaran PPKN Melalui Metode Pembelajaran Teams Games Tournament di SMP Negeri 10 Palembang - Qomariah, Nurul; Waluyati, Sri Artati; Saputra, Ardiansyah (Jurnal Ilmiah Wahana Pendidikan, 2024)
Through the Cooperative Learning model of Teams Game Tournament (TGT), this research aims to enhance the level of classroom engagement in Civic Education. Using the Kemmis and McTaggart model, this study takes the form of Classroom Action Research. The research subjects consist of seventh-grade students from SMP Negeri 10 Palembang, comprising eight male students and thirteen female students. Data collection for this research utilized observation and documentation techniques. Data analysis techniques employed both quantitative and qualitative descriptive methods. Based on the research findings, the TGT cooperative learning model effectively improved the learning activities of seventh-grade students at SMP Negeri 10 Palembang. The average pre-action learning activity score was 48.15, which increased to 60.52 in Cycle I and 75.66 in Cycle II. Meanwhile, the proportion of pre-action learning activities was 28.57 percent, which increased to 71.43 percent in Cycle I and 85.71 percent in Cycle II.